Risk factors for clozapine‐induced myocarditis and cardiomyopathy: A systematic review and meta‐analysis. (4th February 2022) - Vickers, Mark; Ramineni, Vinay; Malacova, Eva; Eriksson, Lars; McMahon, Kirsten; Moudgil, Vikas; Scott, James; Siskind, Dan
Abstract: Objective: Clozapine is the most effective medication for treatment‐refractory schizophrenia, but it is associated with severe cardiac adverse events including myocarditis and cardiomyopathy. To aid treatment decision‐making for clinicians, patients and their carers, we conducted a systematic review and meta‐analysis to identify potential risk factors for clozapine‐induced myocarditis and cardiomyopathy. Methods: A systematic search was conducted of PubMed, Embase, CINAHL, Web of Science, Cochrane and PsycInfo for studies reporting myocarditis and cardiomyopathy among people on clozapine and potential risk factors. We calculated pooled effect sizes on risk factors using a random‐effects meta‐analytic model. Risk of publication bias was assessed using the Newcastle‐Ottawa scale. Results: Seven studies met the inclusion criteria, of which six studies had quantitative data included in the meta‐analysis. The odds of clozapine‐induced myocarditis increased with concurrent sodium valproate use ( k  = 6, n  = 903, pooled OR 3.58, 95% CI 1.81–7.06), but were not significantly greater with the use of quetiapine, lithium or selective serotonin reuptake inhibitors. Our qualitative review identified conflicting results reported for increasing age and higher clozapine dose as risk factors for myocarditis. No other factors, including genetic risk, sex, ethnicity, smoking, alcohol, substance abuse or cardiometabolic disease, were associated with greater odds of myocarditis. No risk factors for cardiomyopathy were identified in the literature. Conclusion: Concurrent use of sodium valproate increases the odds of clozapine‐induced myocarditis. Thus, clinicians should consider the temporary cessation of sodium valproate during the initial titration phase of clozapine.